"He told me it would be extremely selfish of me to even consider [having kids]": The importance of reproductive health to women with spina bifida and the lack of support from their providers. Issue 2 (April 2020) - Streur, Courtney S.; Schafer, Christine L.; Garcia, Valerie P.; Quint, Elisabeth H.; Sandberg, David E.; Kalpakjian, Claire Z.; Wittmann, Daniela A.
Abstract: Background: As more women with spina bifida (SB) enter their reproductive years, the number having children is significantly increasing. However, little is known about their understanding of their ability to get pregnant or their experiences in considering, planning, or interacting with providers during a pregnancy. Objective: We sought to determine what women have been told and understand about their reproductive health, their attitudes towards having children, and their experiences interacting with providers when seeking reproductive health care. Methods: In this exploratory study employing qualitative research methods and following Grounded Theory, interviews with women with SB 16 years or older were transcribed verbatim and analyzed by three coders. Results: Interviews of 25 women with SB ages 16–52 (median 26) revealed the following themes about their reproductive health perceptions and experiences: 1) poor understanding of reproductive health and potential, 2) interest in having a family, 3) facing provider's opposition to their reproductive goals, 4) going into pregnancy and delivery unprepared, 5) the importance of provider support for reproductive goals. Five women experienced an unintended pregnancy. Conclusions: Although having children is important to most women with SB in this study, they report a poor understanding of their reproductive potential with several noting unintended pregnancies. They feel uninformed and unprepared during pregnancy and face discouragement from providers. Those experiencing supportive providers report a more positive experience. This demonstrates the urgent need to educate women with SB about their reproductive health and the providers who care for them how to support and counsel these women.